Efficacy of Different Therapeutic Regimens in Subclinical Endometritis in Cross Bred Dairy Cows - Malik, Asloob Ahmad; Yousuf, Nahida; Sofi, Khursheed Ahmad; Naikoo, Mehrajuddin; KHatun, Arjuma (The Indian Journal of Animal Reproduction, 2024)
The present study was conducted on cross bred cows (n=30) having completed 60 days postpartum to assess the efficacy of different treatments in subclinical endometritis in crossbred dairy cows. A total of 20 animals that tested positive for subclinical endometritis (SCE) on endometrial cytology and white side test were sub divided into three treatment groups corresponding to Group I-III. The Group IV consisting of 10 healthy animals without any uterine infection served as control in which AI was performed on day of estrus. In Group I, single intrauterine dose of cephapirin benzathine (500mg), Group II Levofloxacin @ 4-5 mg/kg bw i.m. and Group III Lugol’s Iodine (0.5%) @ 30ml I/U for 3 consecutive days were given, respectively. In first three groups, WST was conducted on subsequent estrus and animals testing negative were subjected to AI. Treatment efficiency was evaluated on the basis of first service conception rate. In Group I, Group II, Group III and Group IV first service conception rate was 50%, 40%, 33.33% and 60% respectively. FSCR was non significantly (P>0.05) higher in animals treated with cephapirin benzathine compared to other treatment groups. It was concluded that cephapirin benzathine is the most suitable treatment of SCE but Lugol’s Iodine can be recommended for treatment of SCE and improving conception rate.
Keywords: Cephapirin benzathine; Cross bred cows; Lugol’s Iodine; Repeat breedin; Subclinical endometritis